Comparison of inter-trial recovery times for the determination of critical power and W` in cycling - Karsten, B.; Hopker, J.; Jobson, S. A.; Baker, J.; Petrigna, L.; Klose, A.; Beedie, C. (Journal of Sports Sciences, 2014)
Critical Power (CP) and W` are often determined using multi-day testing protocols. To investigate this cumbersome testing method, the purpose of this study was to compare the differences between the conventional use of a 24-h inter-trial recovery time with those of 3 h and 30 min for the determination of CP and W`. Methods: 9 moderately trained cyclists performed an incremental test to exhaustion to establish the power output associated with the maximum oxygen uptake (pmax), and 3 protocols requiring time-to-exhaustion trials at a constant work-rate performed at 80%, 100% and 105% of pmax. Design: Protocol A utilised 24-h inter-trial recovery (CP24/W`24), protocol B utilised 3-h inter-trial recovery (CP3/W`3), and protocol C used 30-min inter-trial recovery period (CP0.5/W`0.5). CP and W` were calculated using the inverse time (1/t) versus power (P) relation (P = W`(1/t) + CP). Results: 95% Limits of Agreement between protocol A and B were -9 to 15 W; -7.4 to 7.8 kJ (CP/W`) and between protocol A and protocol C they were -27 to 22 W; -7.2 to 15.1 kJ (CP/W`). Compared to criterion protocol A, the average prediction error of protocol B was 2.5% (CP) and 25.6% (W`), whilst for protocol C it was 3.7% (CP) and 32.9% (W`). Conclusion: 3-h and 30-min inter-trial recovery time protocols provide valid methods of determining CP but not W` in cycling.